Effects of Salmonella Typhimurium infection on intestinal flora and intestinal tissue arachidonic acid metabolism in Wenchang chickens - Chen, Shenghong; Xie, Yaochen; Guo, Dingqian; Li, Tiansen; Tan, Zhen; Ran, Xuhua; Wen, Xiaobo (Frontiers in Microbiology, 2025)
Salmonella infections can lead to intestinal inflammation and metabolic disorders in birds. However, whether arachidonic acid (ARA) metabolism is involved in Salmonella-induced intestinal inflammation remains unclear. This experiment investigated the changes in cecal flora and ARA metabolism in Hainan Wenchang chickens infected with S. Typhimurium using 16s rDNA sequencing and targeted metabolomics. The results showed that the levels of ARA metabolites were increased in the cecum tissue of Wenchang chickens after infection with S. Typhimurium, including prostaglandin E2 (PGE2), prostaglandin F2α (PGF2α), lipoxin A4 (LXA4), ± 8(9)-EET, ± 11(12)-EET, and ± 8,9-DiHETrE. The content of key enzymes for ARA production and metabolism (Phospholipase A2 PLA2 and Cyclooxygenase-2 COX-2) in chicken cecum tissues was increased after S. Typhimurium infection. The relative mRNA levels of inflammatory factors were also increased after infection, including Interferon-γ (IFN-γ), Transforming growth factor-β1 (TGF-β1), Interleukin-4 (IL-4), and Interleukin-6 (IL-6). In HD11 cells, the use of a cyclooxygenase (COX) inhibitor reduced the increased levels of COX-2 and PGF2α induced by S. Typhimurium infection and effectively reduced the inflammatory response. In addition, the number of beneficial genera (e.g., Bifidobacterium, Lactobacillus, and Odorobacterium) in the cecum of Wenchang chickens was significantly reduced after infection with S. Typhimurium. The present study revealed the structure of cecal flora in S. Typhimurium-infected Wenchang chickens. In addition, this study demonstrated that S. Typhimurium activates the ARA cyclooxygenase metabolic pathway, which in turn mediates the development of intestinal inflammation in Wenchang chickens. The results can provide data support and theoretical support for the prevention and control of avian salmonellosis.